Decadal Changes and Future Projections of Precipitation in the Metropolitan Area of Milwaukee - (:unkn) unknown (My University, 2012)
This research investigated decadal changes and future projections of precipitation in the Metro Milwaukee and surrounding area, the largest urban area in Wisconsin. Spatial and temporal precipitation patterns derived for the Metro Milwaukee from the high-resolution gridded historical climatic dataset for Wisconsin were analyzed for 1950-2006. In addition, precipitation scenarios were generated via statistical downscaling of the Third Generation Coupled Global Climate Model (CGCM3) outputs. The delta method was chosen for the statistical downscaling of the CGCM3 output for the two future time periods, 2041-2070 (2050s) and 2071-2100 (2080s). The Mann-Kendall test and the Sen's slope test were applied to investigate trends of annual and extreme precipitation. The gridded historical data were interpolated with an inverse distance weighting algorithm for spatial analysis. The annual precipitation was projected to increase by 6% to 14% by the 2050s and by 8% to 12% by the 2080s. The regional analysis of annual precipitation showed that the northern regions receive less precipitation compared to the average of the study area, and the southern regions receive more. The 95th percentile of each year's daily total precipitation was projected to increase in the future. The projected changes in extreme precipitation were higher than those simulated for the annual precipitation changes. Based on the spatial patterns of annual and monthly precipitation, and the predominant wind direction, a pattern of higher precipitation amounts down-wind from the city could be observed for the historical climate dataset for 1950-2006.
Keywords: Climate Change; Milwaukee; Wisconsin; Precipitation changes; Statistical Downscaling